Sociocultural Representation in the Use of Speech Acts - Sutikno, Bellatrix Angelicamila; Setyorini, Ajeng; Hidayat, Nur (Journal of English Language and Education, 2024)
This research explores analyse the word speech action by socio-cultural approach that values frequently found in the novel "Totto-Chan: The Girl at the Little Window" by The goal of this speech action study is to analyse speech actions containing sociocultural Tetsuko Kuroyanagi. The study employs Leech's theory of speech acts, which centres on the theory of speech actions. This study uses a qualitative methodology. The data analysis approach utilizes both primary and secondary data, collected from the object of study—in this case, the novel "Totto-Chan: The Girl at the Little Window." The method of collecting data involves sorting and classifying information from study materials, such as books or transcripts, into primary and secondary data categories. Additionally, phrase sentences containing sociocultural components are analyzed. The analysis's findings demonstrate the extent to which a variety of sociocultural elements, including speech action, impact speech action. Trust and culture are the two most important variables influencing speech development and people's attitudes towards speaking up and taking action.